EFEKTIVITAS BERBAGAI FUNGI MIKORIZA ARBUSKULAR INDIGENUS TERHADAP SERAPAN HARA P DAN PERTUMBUHAN TANAMAN JARAK PAGAR (Jatropha curcas L.) - Muzakkir Muzakkir; Eti Farda Husin; Agustian Agustian; Auzar Syarif (Jurusan Tanah Fakultas Pertanian Universitas Andalas, 2010)
Utilization of arbuscular mycorrhizae fungi (FMA) is an alternative way to improve soil fertility. Therefore, it must be developed by studying deeply the effectivity of the FMA. This is important due to either its ability to associate with almost all of vegetation family in terrestrial ecosystems or its ability to increase plant growth rate, seedlings quality, and crop yield, especially on critical land. A research about effectivity of variously indigenous arbuscular mycorrhizae fungi on P-sorption and Jatropha growth was conducted at laboratorium and glasshouse Agriculture Faculty, Andalas University. This research was aimed to gain the most effective isolate of arbuscular mycorrhizae fungi on growth of and P-sorption by Jatropha (Jatropha curcas L.) plant on critical land. Single isolat such as Glomus sp2, Acaulospora sp1, Gigaspora sp1, and compound isolate M7 (Glomus sp2,+ Acaulospora sp1 + Gigaspora sp1) significantly affected plant height, canopy dry matter, infection percentage and intensity, and P-sorption. M7 Compound isolate was the most effective innoculum. By this isolate, height of Jatropha seedlings was 27.5 cm, canopy dry matter 5.9 g, infection percentage 78.5%, infection intensity was 49.1, and P-sorption by canopy was 1.6 g for each seedling. Keywords: Effectiveness of FMA